2003
DOI: 10.1002/clc.4960261205
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function is associated with presence and severity of coronary atherosclerosis

Abstract: SummaryBackground: Overt hypothyroidism has been found to be associated with cardiovascular disease. Moreover, subclinical hypothyroidism is a strong indicator of risk for aortic atherosclerosis and myocardial infarction.Hypothesis: We hypothesized that variation of thyroid function within the normal range may influence the presence and severity of coronary atherosclerosis.Methods: We studied a total of 100 consecutive men and women (59 men, 41 women, age 63.7 ± 11.0 years) who underwent coronary angiography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 26 publications
5
77
2
5
Order By: Relevance
“…Perhaps more importantly, data regarding left ventricular systolic function were not provided, an important drawback in light of the well-known consequences of heart failure on the thyroid system. 2,3 Our study lends support to the theory advanced by Auer et al 5 in so far as we confirmed their results in a large cohort of patients in whom the impact of potential confounders was minimized by applying stringent exclusion criteria. The reduction in fT3 levels observed in patients with CAD could be interpreted simply as a marker of disease rather than as an element contributing directly to disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps more importantly, data regarding left ventricular systolic function were not provided, an important drawback in light of the well-known consequences of heart failure on the thyroid system. 2,3 Our study lends support to the theory advanced by Auer et al 5 in so far as we confirmed their results in a large cohort of patients in whom the impact of potential confounders was minimized by applying stringent exclusion criteria. The reduction in fT3 levels observed in patients with CAD could be interpreted simply as a marker of disease rather than as an element contributing directly to disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings showed a significant and positive association between baseline OPG and baseline vWF or TSH in hypothyroid patients (Table 2). Since vWF is a reliable parameter for endothelial vascular injury (17 -21), particularly in hypothyroid patients (21), these findings support the notion that an increase in serum OPG levels is also a reliable marker for vascular injury in hypothyroidism (8,9). However, the baseline level of vWF, but not that of TSH, was significantly and independently negatively associated with the change in serum OPG during 1 year of euthyroidism (Table 4).…”
Section: Discussionmentioning
confidence: 55%
“…Hypothyroidism, even in its latent form, is associated with increased morbidity from cardiovascular disease (8,9). We recently reported that intima-media thickness (IMT) in the common carotid artery, a good predictor for cardiovascular events (10,11), is increased in hypothyroid patients, and that increased IMT normalized after one year of levothyroxine (L-T4) replacement therapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Auer and cols. (12) showed that higher serum fT4 levels were inversely correlated with the severity of coronary atherosclerosis and higher thyrotropin levels correlated positively. The reasons proposed to underlie the differences in the study results are as follows: i) study populations that are too small to detect an association between subtle changes in fT4 level and coronary atherosclerosis because of the narrow reference range for serum fT4 level; ii) inclusion of heterogeneous patient groups having either stable angina pectoris or acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…While TH indirectly modifies atherosclerotic risk factors such as lipid profile (2,3) and blood pressure (4), direct effects act via vascular smooth muscle cells, altering vascular tone (5), angiotensin-II type 1 receptor modulating the proliferation of vascular smooth muscle cells (6), upregulation of basic fibroblast growth factor causing enhanced angiogenesis (7), modulating the maturation and functioning of macrophages (8), and acting on the renin-angiotensin system (9,10). However, clinical studies yield conflicting results and mechanistic explanations remain elusive (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%